Foreign Funded NGOs in Russia, Belarus and Ukraine: Recent Restrictions and Implications - Olga Oleinikova (Cosmopolitan Civil Societies: An Interdisciplinary Journal, 2017)
The opportunity for public participation through NGO action in post-communist societies is continuously starved by legal framework. Since the collapse of Soviet Union, NGOs in Russia, Ukraine, Belarus and other post-Communist states have traditionally looked abroad for their funding, and are dismayed at recent legislation setting up new barriers to this practice. This paper discusses the new laws and restrictive amendments to legislative acts on the operations of foreign funded NGOs in Russia, Belarus and Ukraine, adopted since 2011.